Studi Kasus Kepemimpinan Kepala Sekolah Terhadap Literasi Siswa Sekolah Dasar - Prapti, Suprapti; Darmuki, Agus; Surachmi, Sri (Universitas Sarjanawiyata Tamansiswa, 2024)
This research delves into the leadership strategies employed by the principal of SD Negeri 3 Suru to enhance literacy activities within the school. Utilizing a qualitative case study approach, interviews and documentation reveal various initiatives implemented by the principal, such as the